Spatial Upgrading of Riverbank Slums Towards Sustainability of Watershed Infrastructure - Mukaromah, Hakimatul; Permana, Chrisna T; Sa'adah, Zumrotus (Department of Urban and Regional Planning, Diponegoro University, 2025)
Due to limited land availability, riverbanks are frequently the preferred location for the establishment of slums or squatters. The expansion of these areas can diminish the capacity and sustainability of urban drainage system. It is envisaged that the upgrading of slum settlements on riverbanks will not only enhance livelihood levels but also contribute to the watershed's sustainability as primary drainage. The research study area is Kampong Mojo, a pilot project for slum upgrading along the Bengawan Solo River. This article seeks to determine how slum upgrading and infrastructure can contribute to the sustainability of the Bengawan Solo watershed’s supporting infrastructure. In this study, qualitative and spatial analysis were utilized, with data support provided by field observations, interviews, and document research. Furthermore, data and information will be analyzed in three stages: (1) mapping the land use change of infrastructure and settlement along the river; (2). identification of settlement riverside upgrading models; and (3). analyzing the relevance of settlement planning on the sustainability of the watershed infrastructure. The findings of this study indicate that, for a river to function optimally as a primary drainage and flood control system, it is essential to promote the development of watershed-supporting infrastructure by strategically structuring land use along the river and enhancing the community’s capacities. This study highlights the significance of an integrated approach to slum management, thereby facilitating the government's capacity to implement more inclusive and sustainable riverbank management.